2015
DOI: 10.1177/0142723714566335
|View full text |Cite
|
Sign up to set email alerts
|

Developing linguistic flexibility across the school years

Abstract: The study examined linguistic flexibility of Hebrew-speaking students from middle childhood to adolescence compared with adults on tasks requiring them to alternate between different versions of varied linguistic stimuli. Lexical flexibility was tested by constructing different words with a shared root and a shared prosodic template; Hebrew-specific morpho-syntactic abilities were tested by alternating between bound inflected and free syntactic forms of verbs and nouns; syntactic tasks involved shifting betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Various forms of metalinguistic awareness have been proven beneficial for reading, including phonemic awareness (see Ehri, Nunes, Stahl, & Willows, 2001), morphological awareness (Carlisle, 1995), and syntactic awareness (Gaux & Gombert, 1999;Nation & Snowling, 2000;Tunmer, Nesdale, & Wright, 1987). More recently, Kaplan and Berman (2015) confirmed that linguistic flexibility is an important facet of later language development. One theory for why metalinguistic awareness improves reading ability is that MA training causes students' thinking about the meanings of words and sentences in and out of text to become less rigid, more active, and more flexible (Cartwright, 2008).…”
Section: Metalinguistic Awarenessmentioning
confidence: 99%
“…Various forms of metalinguistic awareness have been proven beneficial for reading, including phonemic awareness (see Ehri, Nunes, Stahl, & Willows, 2001), morphological awareness (Carlisle, 1995), and syntactic awareness (Gaux & Gombert, 1999;Nation & Snowling, 2000;Tunmer, Nesdale, & Wright, 1987). More recently, Kaplan and Berman (2015) confirmed that linguistic flexibility is an important facet of later language development. One theory for why metalinguistic awareness improves reading ability is that MA training causes students' thinking about the meanings of words and sentences in and out of text to become less rigid, more active, and more flexible (Cartwright, 2008).…”
Section: Metalinguistic Awarenessmentioning
confidence: 99%
“…teachers in relation to their acquisition of the language for the specific purposes of linguistics as an academic register. Register flexibility is understood as an individual productive skill which pertains to the capacity of the speaker for fast and controlled adjustments of language use based on sensitivity for changing communicative goals and circumstances (Kaplan and Berman, 2015;Qin and Uccelli, 2020). Methodologically, the project combines written elicitation tasks with a grammar test (TEDS-LT) evaluating the development of linguistic terminology and declarative grammar knowledge (Bremerich-Vos et al, 2011).…”
Section: Development Of Productive Register Variation In German Bache...mentioning
confidence: 99%
“…It explores the register flexibility of students (mainly native speakers of German) recruited from a bachelor program for primary school teachers in relation to their acquisition of the language for the specific purposes of linguistics as an academic register. Register flexibility is understood as an individual productive skill which pertains to the capacity of the speaker for fast and controlled adjustments of language use based on sensitivity for changing communicative goals and circumstances (Kaplan and Berman, 2015 ; Qin and Uccelli, 2020 ).…”
Section: Experimental Approaches: Isolating Intra-individual Variabilitymentioning
confidence: 99%
“…Note that this is a rather conservative estimate: we know that language development begins before age 1 ( Jusczyk, 1997 ; Karmiloff and Karmiloff-Smith, 2001 ) and continues throughout childhood and adolescence ( Nippold, 1998 ; Berman, 2004 , 2007 ; Nippold et al, 2005 ; Kaplan and Berman, 2015 ); moreover, children are exposed to language—through utterances directed to them, utterances directed to other people present, radio and television, and later school, reading and the internet almost every waking hour of their lives.…”
Section: Arguments For Ugmentioning
confidence: 99%